Controlling spacing of double-ring perfect optical vortex using the Fourier transform of Bessel beam with axicon phase. (February 2023) - Yang, Kaibo; Luo, Hao; Li, Peng; Wen, Feng; Gu, Yuzong; Wu, Zhenkun
Highlights: Our paper reports on a double-ring vortex beam with adjustable spacing between the two rings. Its size is also only minimally affected by the change of topological charge. The ring spacing between two rings can be modulated via the conical parameter. We also consider the vortex array created by the double-ring beam, as well as the beam's shape. Abstract: The perfect optical vortex (POV) has additional potential uses in optical trapping and optical communication, due to its diameter being independent of its topological charge. In this study, we demonstrate a double-ring vortex beam with adjustable spacing between the two rings; its size is also only minimally affected by the change of topological charge. To our knowledge, the beam satisfies the double-ring POV concept. The Fourier transform of a Bessel beam embedded with an axicon phase can theoretically produce such a beam. The experimental findings support the numerical results, demonstrating that the ring spacing between two rings can be modulated via the conical parameter, expanding the superposition of double-ring beams and that the two rings always keep the same topological charge value. We also consider the vortex array created by the double-ring beam, as well as the beam's shape. Optical trapping, orbital angular momentum multiplexing, and optical communication could all benefit from the changeable ring spacing of a double-ring vortex beam.